MÉTODO MONTESSORI Y SU IMPACTO EN LA LECTURA EN LOS ESTUDIANTES DE 4TO AÑO DE EDUCACIÓN BÁSICA - BUSTAMANTE AREVALO, LYZA MARIA (2024)
María Montessori's methodological approach is fascinating due to its emphasis on autonomy, freedom and respect for the integral growth of children, supported by efficient and detailed observations of child development. In addition to the above, this method is based on the rigorous reflection of the child's progressive process, based on this, it attempts to offer students a form of learning appropriate to their pace and interests. This study sought to delve deeper into the impact of Montessori methods on the reading skills of 4th grade students at the "Guayaquil" school in the Vinces canton. The mixed research approach (qualitative-quantitative), both descriptive and explanatory, was used, using bibliographic sources, field studies and non-experimental analysis. The study population was 40 fourth grade students at the "Guayaquil" School. To collect data, interviews were carried out with 2 teachers from the institution to evaluate their understanding of the Montessori methodology, while a survey was administered to the students to identify possible difficulties in reading. From this research, it is anticipated that the Montessori approach to teaching reading will be characterized by a dynamic and engaging educational process.